Parity is associated with a longer time to reach irreversible disability milestones in women with multiple sclerosis. (September 2015) - Masera, S; Cavalla, P; Prosperini, L; Mattioda, A; Mancinelli, CR; Superti, G; Chiavazza, C; Vercellino, M; Pinessi, L; Pozzilli, C
Background: Multiple sclerosis (MS) frequently affects women of childbearing age. While short-term effects of pregnancy on MS course are well-known, whether pregnancy may influence long-term disability progression is debated. Methods: A two-centre retrospective study to investigate long-term effect of pregnancy on disability was performed in a population of MS women. Survival analyses and multivariate Cox proportional regression models (including early predictors of MS severity and exposure to disease-modifying treatments) were performed to compare time to reach well-established disability milestones in nulliparous women and in those with pregnancies after MS onset ('parous'). Women with pregnancies before MS onset were excluded from analyses as they represent a heterogeneous group. Results: Data about 445 women (261 nulliparous, 184 'parous') were analysed. A longer time to reach Expanded Disability Status Scale (EDSS) 4.0 and 6.0 was observed in parous women; Cox regression models revealed a lower risk for 'parous' than nulliparous women in reaching EDSS 4.0 and 6.0 (HR = 0.552, p = 0.008 and HR = 0.422, p = 0.012 respectively). Conclusion: Our findings suggest that pregnancy after MS onset is associated with a slower long-term disability progression. Whether this represents a biological/immunological effect, or reflects a higher propensity toward childbearing in women with milder disease, it remains uncertain deserving further investigations.